PENGARUH PENGELUARAN PEMERINTAH DI BIDANG KESEHATAN DAN PENGELUARAN PEMERINTAH DI BIDANG PENDIDIKAN TERHADAP KEMISKINAN DI PROVINSI KALIMANTAN SELATAN - RINANDA KINANTI (PPJP Universitas Lambung Mangkurat, 2018)
This study suggests the influence of government spending on education and health on poverty in South Kalimantan Province in 2012-2016. Poverty is a big and basic problem. Therefore, the purpose of this study looks at how the effects or effects of education and health spending on poverty are affected. Panel data to be used in this research. The fixed effect model (FEM) approach becomes the analytical method used in this study by using multiple linear regression analysis method. And using the Simultaneous Test (Test F), Individual Test (Test t) and Test R-Square (R2). Based on the result of research estimation of expenditure or expenditure from government of field that is education and health together have a significant influence to poverty and the most dominant factor influencing poverty is government expenditure in health sector.Keywords : Poverty, Government Expenditure on Education, Government Expenditure on Health.